204 DEDICATED NURSING HOME SERVICE IN A TERTIARY HOSPITAL: EFFECT ON ADMISSION NUMBERS AND LENGTH OF STAY. (25th October 2022) - Mahon, CM; Ryan, M; Kennelly, SM; Martin, R
Abstract: Background: In 2019 a dedicated Nursing Home (NH) in-patient service was established in a tertiary hospital, comprising a Consultant Geriatrician, clinical nurse specialist, NCHD and administrative support. All NH residents over 65 with medical diagnoses were admitted by the NH team who also provide a consult service for NH residents under other specialties. Methods: Data were sourced from the Hospital Inpatient Enquiry system on length of stay of patients identified as admitted from a nursing home compared to those admitted under the NH team and their average lengths of stay over 2019-2021. Results: In 2019, 749 NH residents were admitted to hospital with an average length of stay (ALOS) of 7.93 days, the NH inpatient service was established in July 2019 and showed a reduction of ALOS from 9.25 to 6.6 days in the 6 months following its establishment (29% difference.) In 2020, 707 NH residents were admitted with 352 admitted under the NH team. The ALOS of NH residents admitted under the NH team was 5.66 days in 2020 compared to 8.65 overall (35% difference.) In 2021, 765 NH residents were admitted with 402 under the NH team. ALOS of NH residents admitted under the NH team was 5.33 days in 2021 compared to 8.28 overall (36% difference.) Conclusion: Within six months of its commencement the dedicated NH service had decreased length of stay by 29%. The average length of stay across all services has decreased year on year from 6.6 to 5.3 days from 2019 to 2021. The ALOS in the total cohort (including residents admitted surgically and those under 65) was 29-36% higher. Though difficult to accurately compare these cohorts due to different presenting diagnoses and medical backgrounds in those admitted surgically or those under 65, the overall reduction in length of stay over the three years does highlight the benefit from this dedicated service.